2017
DOI: 10.1016/j.pscychresns.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of graphic cigarette warning labels predict smoking cessation relapse

Abstract: Exposure to graphic warning labels (GWLs) on cigarette packaging has been found to produce heightened activity in brain regions central to emotional processing and higher-order cognitive processes. The current study extends this literature by using functional magnetic resonance imaging (fMRI) to investigate neural activation in response to GWLs and use it to predict relapse in an evidence-based smoking cessation treatment program. Participants were 48 treatment-seeking nicotine-dependent smokers who completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Data on striatal circuit function have shown their potential to predict relapse in smokers [19][20][21]. For instance, blunted brain responses of dorsal striatum and medial/dorsolateral prefrontal cortex (mPFC and dlPFC) to pleasant vs. cigarette-related stimuli predict relapse in smokers [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on striatal circuit function have shown their potential to predict relapse in smokers [19][20][21]. For instance, blunted brain responses of dorsal striatum and medial/dorsolateral prefrontal cortex (mPFC and dlPFC) to pleasant vs. cigarette-related stimuli predict relapse in smokers [21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, blunted brain responses of dorsal striatum and medial/dorsolateral prefrontal cortex (mPFC and dlPFC) to pleasant vs. cigarette-related stimuli predict relapse in smokers [21]. Further, brain responses in the ventromedial PFC to graphic warning labels, relative to a visual control image, predicted relapse in treatment-seeking nicotinedependent smokers [19]. However, functional magnetic resonance imaging (MRI) cannot identify the structural connections between those circuits.…”
Section: Introductionmentioning
confidence: 99%
“…26,28 The finding that neural activity in subregions of the MPFC implicated in self-related processing and valuation is associated with subsequent sharing engagement brings together previously disconnected findings that highlight the importance of interpersonal communication about mass media campaigns, 8,9,59,60 and research showing that brain activity within the MPFC during message exposure is related to subsequent behavior change. [12][13][14][15]28,61 Prior neuroimaging studies have identified subregions of the MPFC that are preferentially engaged during various types of self-related tasks, including the retrieval of autobiographical memories 32,33 and engagement in explicit and implicit self-referential thoughts. 34−38 Recent research has also shown that brain activity in these same regions is implicated in intentions to share health news in young adults, 23,24 suggesting that self-relevance may be one important antecedent to decisions to share.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the obtained results have shown, through the estimation of the investigated indexes (i.e., Effort Index), the occurrence of a peculiar neural activation in the prefrontal cortex in response to antismoking advertising. There have been many studies which have demonstrated that the average neural activity in the medial prefrontal cortex (MPFC) during messaging has been associated with future healthier behaviour change in individuals (e.g., for smoking reduction [ 97 ], physical activity [ 98 ]), as well as population measures of antismoking campaigns effectiveness (e.g., online click-through-rates [ 99 ] and calls to quit lines [ 100 ]). Given the multiple psychological functions supported by MPFC [ 101 ], examining the functional connectivity, specifically within the brain's value system can provide additional information about why and how certain types of messages, like graphic warning messages, exert their effects.…”
Section: Discussionmentioning
confidence: 99%